(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
It is known that Sadriddin Aini not only actively promoted the heritage of Alisher Navoi, published works of the thinker, but also carried out large-scale scientific work on the literary relations of the Uzbek and Tajik peoples. One of them is the study of the scientist "Alisher Navoi and Tajik literature."It should be noted that the rich literary heritage of Sadriddin Aini is of special importance in the development of prose, poetry, literary criticism and linguistics.